2002
DOI: 10.1038/sj.onc.1205524
|View full text |Cite
|
Sign up to set email alerts
|

p14ARF regulates E2F activity

Abstract: The ARF protein product of the ink4a/arf locus is induced by a variety of oncogenic signals. ARF facilitates growth arrest through the p53 pathway by hindering the down-regulation of p53 activity mediated by MDM2, through the formation of a protein complex with MDM2. Here we have explored the possibility that human p14 ARF activity is integrated with growth regulating pathways other than p53, and report our results that p14 ARF can control the activity of the E2F transcription factor. p14ARF regulates E2F acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 47 publications
(82 reference statements)
4
49
0
Order By: Relevance
“…The E2F transcription factor can activate p14 ARF gene expression and initiate a p53-dependent response (Bates et al, 1998). Furthermore, we and others have demonstrated that p14 ARF associates with E2Fs and its DP1 regulatory partner and regulates their localization and degradation leading to an inactive E2F1 protein (Eymin et al, 2001;Martelli et al, 2001;Datta et al, 2002;Mason et al, 2002). Collectively, these observations demonstrate that p14 ARF interferes in a direct or indirect manner with some effectors of the RB signalling pathway to control cell growth.…”
Section: Introductionsupporting
confidence: 52%
“…The E2F transcription factor can activate p14 ARF gene expression and initiate a p53-dependent response (Bates et al, 1998). Furthermore, we and others have demonstrated that p14 ARF associates with E2Fs and its DP1 regulatory partner and regulates their localization and degradation leading to an inactive E2F1 protein (Eymin et al, 2001;Martelli et al, 2001;Datta et al, 2002;Mason et al, 2002). Collectively, these observations demonstrate that p14 ARF interferes in a direct or indirect manner with some effectors of the RB signalling pathway to control cell growth.…”
Section: Introductionsupporting
confidence: 52%
“…Nevertheless, a number of follow-up studies clearly demonstrated that this is not entirely the case. In particular, distinct members of E2F family of transcription factors were suggested to be critical downstream targets of p53-independent growth arrest programmes engaged by p14 ARF (Eymin et al, 2001;Martelli et al, 2001;Mason et al, 2002;Rowland et al, 2002). Furthermore, a delay in S-phase progression with consecutive accumulation of cells in G1 phase of the cell cycle upon expression of p14 ARF was shown to occur independently of p53 (Yarbrough et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…22 Similarly, various human tumours exhibit simultaneous loss of p53 and ARF, 24,25 and p14ARF has been reported to limit S-phase progression and colony formation in p53-null human cancer cells. [26][27][28] p19ARF can also inhibit the processing of ribosomal RNA, 29 and the murine and/or human ARF protein interact with other regulators including the E2F transcription factors, 30,31 spinophilin, topoisomerase I, cyclin G, MdmX, 2005; Vol. 4 Issue 3 HIF-1α, pex19p, CARF, p120 E4F , B23, tat-binding protein and Werner's helicase.…”
Section: Introductionmentioning
confidence: 99%